2018
DOI: 10.1016/j.jvs.2018.03.418
|View full text |Cite
|
Sign up to set email alerts
|

Management of failed endovascular aortic aneurysm repair with explantation or fenestrated-branched endovascular aortic aneurysm repair

Abstract: Objective: The incidence of failed endovascular aneurysm repair (EVAR) is increasing, and understanding the different methods of management and repair is paramount. The objective of this study was to evaluate the clinical management and rescue of failed EVAR by either explantation or fenestrated-branched EVAR (F/B-EVAR).Methods: A retrospective analysis (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) of 247 patients who underwent either explantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Varying rates of technical success were reported. [4][5][6]10,22,[24][25][26][27] Wang et al recently reported a 100% technical success rate in six patients after fenestrated EVAR for previously failed EVAR and in six after previous open repair. 24 Similar to our experience, Wang et al did not find a difference between the technical success rates after post-open or post-endo fbEVAR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Varying rates of technical success were reported. [4][5][6]10,22,[24][25][26][27] Wang et al recently reported a 100% technical success rate in six patients after fenestrated EVAR for previously failed EVAR and in six after previous open repair. 24 Similar to our experience, Wang et al did not find a difference between the technical success rates after post-open or post-endo fbEVAR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…15 Fenestrated-branched endovascular aortic aneurysm repair is presently a first treatment option in high surgical risk patients and in those with failed EVAR or previous OSR. 1,2,23 Despite being technically demanding, the use of IL custom-manufactured device overcomes the anatomical limitations of short-body initial grafts and short distance between lowest TVV and bifurcation, leading the fixation inside the endograft. As reported in our series, a short-body graft does not ensure a stable overlap, 2 which normally requires 6 to 7 cm, and does not allow neither a tube graft below FB-EVAR nor a standard EVAR inside the preexisting devices.…”
Section: Discussionmentioning
confidence: 99%
“…These methods were extremely used all over the world [10]. However, failure of these grafts occurred during follow-up [11]. Consequently, surgical conversion of these stents became an indication of aneurysm management or obligation for life-saving.…”
Section: Discussionmentioning
confidence: 99%